Soils surrounding saline-alkaline lakes of Nhecolândia, Pantanal, Brazil: Toposequences, mineralogy and chemistry - Costa-Silva, André Renan; Lucas, Yves; Rezende-Filho, Ary Tavares; Ramos, Mariana Dias [UNESP]; Merdy, Patricia; Ishida, Débora Ayumi; Barbiero, Laurent; Melfi, Adolpho José; Montes, Célia Regina (Elsevier, 2024)
The Nhecolândia subregion of the Brazilian Pantanal, subject to a highly seasonal climate, hosts a diverse range of freshwater and saline-alkaline lakes. The latter can be green due to cyanobacterial bloom, black due to dissolved organic matter, or crystalline. Over the past two decades, numerous studies in the region have explored the connections between the lake type, the surrounding soils, and water table dynamics. However, these insights emerged from independent studies conducted at multiple sites, making their synthesis challenging and leaving questions about the differences between lake types. Our research focuses on a representative Nhecolândia site, aiming to comprehensively understand soil and lake genesis and dynamics. For each lake type, we conducted detailed toposequence soil studies, assessing particle size distribution, chemistry and mineralogy of the <2 mm fraction of identified horizons. A 49-month temporal study utilizing PlanetScope satellite data examined lake connections to the hydrographic network affected by seasonal flooding. Our findings confirmed the general organization and mineralogy of soils around saline-alkaline lakes. Notably, we identified variations in soil toposequences corresponding to different lake type. Two types of silcrete were observed: one acidic, found at the upper slopes, and the other alkaline, located at the lower slopes. We determined that, for endorheism and lake alkalinization, the presence of a ridge around a lake is insufficient. Instead, deep impermeable horizons in the lower portion of the toposequences are essential. Additionally, crystalline lakes differentiate from black and green ones due to less efficient hydraulic isolation. Our comprehensive dataset from a single site provides a valuable resource for guiding and developing more specific studies on these alkaline systems.
Keywords: Arenosols; Nhecolândia; Pantanal; Petroduric horizon; Silcrete; Solonetz